The Ultimate Guide to Improving English Learning in Primary School - Fathi Falah; Khuliyah Candraning Diyanah; Aditya Sukma Pawitra; Yeni Dhamayanti; Tania Ardiani Saleh; Babucarr Jassey (Communautaire: Journal of Community Service, 2025)
English learning is a vital skill in the era of globalization. However, many elementary school students struggle with English and show limited interest due to monotonous and less engaging teaching methods. This often leads to low confidence in using the language actively. To address this issue, the English Learning Program (BBI) was implemented to improve the English proficiency of 4th grade students at elementary school. The program introduced interactive and enjoyable teaching strategies through a group-based approach, including language games, conversation practices, songs to introduce parts of the body, and basic grammar lessons. These activities aimed to create a positive learning environment that encourages active participation and boosts student confidence. The results showed increased enthusiasm, participation, and comprehension among students. Many students demonstrated improved ability and willingness to use English in daily conversation. This program highlights the importance of innovative and interactive methods in fostering early interest and language proficiency. It suggests that well-designed, enjoyable approaches can significantly enhance English learning at the elementary school level.